Mapping genetic loci for tolerance to lime-induced iron deficiency chlorosis in grapevine rootstocks (Vitis sp.) - Bert, Pierre-François; Bordenave, Louis; Donnart, Martine; Hévin, Cyril; Ollat, Nathalie; Decroocq, Stéphane (Theoretical and applied genetics, 2013)
Iron is essential to plants for chlorophyll formation as well as for the functioning of various iron-containing enzymes. Iron deficiency chlorosis is a wide-spread disorder of plants, in particular, of those growing on calcareous soils. Among the different ways to control iron deficiency problems for crops, plant material and especially rootstock breeding is a suitable and reliable method, especially for fruit trees and grapes. The aim of the experiment was to characterize the genetic basis of grapevine chlorosis tolerance under lime stress conditions. A segregating population of 138 F1 genotypes issued from an inter-specific cross between Vitis vinifera Cabernet Sauvignon (tolerant) × V. riparia Gloire de Montpellier (sensitive) was developed and phenotyped both as cuttings and as rootstock grafted with Cabernet Sauvignon scions in pots containing non-chlorosing and chlorosing soils. Tolerance was evaluated by chlorosis score, leaf chlorophyll content and growth parameters of the shoots and roots. The experiments were performed in 2001, 2003 and 2006. The plants analysed in 2006 were reassessed in 2007. The most significant findings of the trial were: (a) the soil properties strongly affect plant development, (b) there are differences in tolerance among segregating genotypes when grown as cuttings or as rootstocks on calcareous soil, (c) calcareous conditions induced chlorosis and revealed quantitative trait loci (QTLs) implicated in polygenic control of tolerance, (d) rootstock strongly contributes to lime-induced chlorosis response, and (e) a QTL with strong effect (from 10 to 25 % of the chlorotic symptom variance) was identified on chromosome 13. This QTL colocalized with a QTL for chlorophyll content (R ² = 22 %) and a major QTL for plant development that explains about 50 % of both aerial and root system biomass variation. These findings were supported by stable results among the different years of experiment. These results open new insights into the genetic control of chlorosis tolerance and could aid the development of iron chlorosis-tolerant rootstocks.